2002
DOI: 10.1124/jpet.102.036772
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Characterization of the Activity of Telmisartan: An Insurmountable Angiotensin II Receptor Antagonist

Abstract: In vitro studies have shown that telmisartan is an insurmountable angiotensin II subtype-1 (AT1) receptor antagonist. Herein, the molecular basis of this insurmountable antagonism has been investigated in vitro, and the effect of telmisartan has been compared in vivo with that of irbesartan and candesartan. Association and dissociation kinetics of telmisartan to AT1 receptors have been characterized in vitro on rat vascular smooth muscle cells (RVSMC) expressing solely the AT1 receptor subtype. In a second set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 26 publications
3
38
2
1
Order By: Relevance
“…In contrast, the present data in conscious rats reveal that the effect produced by losartan on the cardiovascular reactivity to orthostatic stress exhibits a profile similar to that of a highly specific AT 1 antagonist (Maillard et al, 2002). Therefore, it is likely that the more pronounced orthostatic hypotensive response described specifically for losartan in the orthostatic stress models reported previously was a consequence of the use of anaesthesia (Ohlstein et al, 1992;Hashimoto et al, 1999;de Moura et al, 2005).…”
contrasting
confidence: 55%
“…In contrast, the present data in conscious rats reveal that the effect produced by losartan on the cardiovascular reactivity to orthostatic stress exhibits a profile similar to that of a highly specific AT 1 antagonist (Maillard et al, 2002). Therefore, it is likely that the more pronounced orthostatic hypotensive response described specifically for losartan in the orthostatic stress models reported previously was a consequence of the use of anaesthesia (Ohlstein et al, 1992;Hashimoto et al, 1999;de Moura et al, 2005).…”
contrasting
confidence: 55%
“…8,9 The ARB telmisartan binds insurmountably to and dissociates slowly from the AT 1 receptor. 10 Other distinguishing features of telmisartan are its almost exclusive biliary excretion and terminal elimination half-life of about 24 h. 11 Clinical studies have shown the ability of once-daily telmisartan to provide effective control of blood pressure. 11 Preclinical studies suggest that telmisartan is highly effective in reducing LVH, [12][13][14][15] and preliminary observations provide evidence for the clinical efficacy of telmisartan in the treatment of LVH at doses that confer effective blood pressure control.…”
Section: Introductionmentioning
confidence: 99%
“…AJ05132; Tran van Chuoi et al 1999) that in the eel does not contain residues associated with losartan binding (Russell et al, 2000). For this reason we used as AT1 antagonist CV11974, which blocks the vascular ANG II-mediated effects in vivo and in vitro (Maillard et al, 2002) and also binds cardiac ANG II receptors in an elasmobranch (Cerra et al, 2001). CV11974, but not GCP42112, abolished the negative inotropism elicited by ANG II, suggesting that it may be mediated by an AT1-like receptor.…”
Section: Transducing Receptors and G Protein Interactionsmentioning
confidence: 99%